A repercussão geral no recurso extraordinário - Amaral, Fernanda Solano do (2011)
The present work analyzes the general repercussion of the subject versed in the extraordinary appeal, as a new admission requirement for the jugdment of the recursal merit (article 102, section 3, of Federal Constitution and articles 543-A e 543-B of Processual Civil Code). It's a obstacle created in Brazilian law as a form to withdraw the automaticity send of the appeals to the Brazilian Supreme Court. With a clearly intention to stop the arrival of thousands of cases that occupy its judgment list. It pursuits a solution to the Supreme Court demand crisis’, moving away from its appreciation, causes of restricted interest to the parts, therefore, in accordance with the new institute, the appeal to the Brazilian Supreme Court passes to be admitted only when show “relevant issues of economic, political, social and legal that exceed the subjective interests of the cause”. It will be verified the importance and greatness of the theme, in comprehension that will be valid for other similar cases without necessity of new appreciation for the Supreme Court and tying the inferior courts. The requirement, therefore, is another step in the search of the effectiveness of the process, in order to rationalize the Supreme Federal Court Work and to give effectiveness and uniformity to its decisions